2019
DOI: 10.35745/ecei2019v2.062
|View full text |Cite
|
Sign up to set email alerts
|

The Application Fuzzy Delphi Method to Summarize Key Factors in the Education of Construction Engineers

Abstract: In addition to the education of STEM (science, technology, engineering, and mathematics), this paper reviews the current relevant courses required in the field of construction projects from the practice point of view. The study summarizes the key courses in the education of construction engineers through document analysis, expert and scholar interviews, and subsequently establishes the key evaluation aspects and index reliability by Fuzzy Delphi Method. This study can provide the basis for the systematic curri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Moreover, Habibi et al [22] applied the FDM to the single round for screening criteria. Hsu et al [23] summarized the key courses in the education of construction engineers, where the evaluation aspects and index are established using the FDM. Ciptono et al [24] classified and identified scientific research and analyzed the current literature on the FDM to gain a broad and detailed understanding of education.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Habibi et al [22] applied the FDM to the single round for screening criteria. Hsu et al [23] summarized the key courses in the education of construction engineers, where the evaluation aspects and index are established using the FDM. Ciptono et al [24] classified and identified scientific research and analyzed the current literature on the FDM to gain a broad and detailed understanding of education.…”
Section: Introductionmentioning
confidence: 99%